Experimental research of mechanical behavior of porcine brain tissue under rotational shear stress. (April 2016) - Li, Gang; Zhang, Jianhua; Wang, Kan; Wang, Mingyu; Gao, Changqing; Ma, Chao
Abstract: The objective of this paper is to investigate mechanical behavior of porcine brain tissue with a series of rotational shear stress control experiments. To this end, several experiments including stress sweep tests, frequency sweep tests and quasi-static creep tests were designed and conducted with a standard rheometer (HAAKE RheoStress6000). The effects of the loading stress rates to mechanical properties of brain tissue were also studied in stress sweep tests. The results of stress sweep tests performed on the same brain showed that brain tissue had an obvious regional inhomogeneity and the mechanical damage occurred at the rotational shear stress of 10–15 Pa. The experimental data from three different loading stress rates demonstrated that the mechanical behavior of porcine brain tissue was loading stress rate dependent. With the decrease of loading stress rate, a stiffer mechanical characteristic of brain tissue was observed and the occurrence of mechanical damage can be delayed to a higher stress. From the results of frequency sweep tests we found that brain tissue had almost completely elastic properties at high frequency area. The nonlinear creep response under the rotational shear stress of 1, 3, 5, 7 and 9 Pa was shown in results of creep tests. A new nonlinear viscoelastic solid model was proposed for creep tests and matched well with the test data. Considering the regional differences, loading stress rates and test conditions effects, loss tangent tan δ in porcine brain tissue showed a high uniformity of 0.25–0.45. Graphical abstract: Highlights: Rotational shear stress control experiments is used with a standard rheometer. We propose a new nonlinear viscoelastic solid model matching well with tests data. Brain tissue shows almost complete elastic properties at high frequency area. Regional inhomogeneity and mechanical damage of brain tissue are strictly studied. Loss tangent tan δ in brain tissue shows a high uniformity of 0.25–0.45.